2019
DOI: 10.1002/nur.21951
|View full text |Cite
|
Sign up to set email alerts
|

Risk of depression in pregnant women with low‐normal serum Vitamin B12

Abstract: High prevalence rates of both Vitamin B12 insufficiency and depressive symptoms exist in pregnant women. Although the association between depressive symptoms and certain nutrient deficiencies like iron, folate, or Vitamin B12 has been established, the specific relationship between low‐normal serum Vitamin B12 levels and depressive symptoms in pregnant women in the United States has not been studied closely. Using 2005–2006 National Health and Nutrition Examination Survey data, a secondary analysis was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
(34 reference statements)
2
6
0
Order By: Relevance
“…We also observed that compared to controls more women with PPD had low normal vitamin B12 (49.8% versus 27.2% in controls; P = 0.001). Similar findings in ante-natal depression is reported recently in 174 pregnant women using secondary data analysis of National Health and Nutrition Examination Survey data, CDC, in USA [ 23 ]. They observed higher frequency of antenatal depression in women with low normal vitamin B12 ( n = 9; 15.2%) compared with those with sufficient vitamin B12 ( n = 6; 5.2%).…”
Section: Discussionsupporting
confidence: 89%
“…We also observed that compared to controls more women with PPD had low normal vitamin B12 (49.8% versus 27.2% in controls; P = 0.001). Similar findings in ante-natal depression is reported recently in 174 pregnant women using secondary data analysis of National Health and Nutrition Examination Survey data, CDC, in USA [ 23 ]. They observed higher frequency of antenatal depression in women with low normal vitamin B12 ( n = 9; 15.2%) compared with those with sufficient vitamin B12 ( n = 6; 5.2%).…”
Section: Discussionsupporting
confidence: 89%
“…We also observed that compared to controls more women with PPD had low normal vitamin B12 (49.8% versus 27.2% in controls; P = 0.001). Similar ndings in ante-natal depression is reported recently in 174 pregnant women using secondary data analysis of National Health and Nutrition Examination Survey data, CDC, in USA (23) . They observed higher frequency of antenatal depression in women with low normal vitamin B12 (n = 9; 15.2%) compared with those with su cient vitamin B12 (n = 6; 5.2%).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, dietary aspects and diet components (ex. vitamin D, folate, selenium intake, iron, vitamin B12, vitamin K, fiber intake, zinc) as well as diet-related inflammatory potential have been linked to depression outcomes [ 161 , 208 , 236 , 312 , 396 , 402 , 403 , 404 , 405 , 406 , 407 , 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 , 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 ]. A poor diet has been linked to depression through mechanisms such as inflammation [ 428 ].…”
Section: Resultsmentioning
confidence: 99%